Jurisdiction and the internet : - Kohl, Uta (Cambridge University Press, 2007)
Does the ability to occupy territory, guard borders, and field militaries give conventional state governments either the right or the competence to control cyberspace? Once upon a time, Kohl (law, U. of Wales-Aberystwyth) was convinced that it did not, then spent some years swirling the question in the back of her head. Now she finds the question very complex, and explains why.